Trauma : excesso, sedução e fantasia na obra de Sigmund Freud - Barbosa, Mônica Adriane (2011)
This dissertation generaly purpose to study the psychic trauma from the Freudian theoretical orientation. Interest in the study of this subject is due to its broad theoretical scope, with its many developments and changes throughout the construction of the psychoanalysis of Freud. In the course of the work a great many texts caught our attention because they present some modification, a plus to be understood. That is to say that Freud's work as a whole, and particularly in reference to this issue, presents itselfes mysterious, not explicit, and is revisited every time a show something more to be understood and integrated with previous knowledge. Especially some texts have increased our curiosity and interest: Project for a Scientific Psychology (1885), Letter to Fliess of September 21, 1897 (letter 69); Interpretation of Dreams, ch. VII (1900/1996); Creative writers and daydreaming (1908/1996), The History of an Infantile Neurosis: The Wolf Man (1918 [1914] / 1996), Beyond the Pleasure Principle (1920/1996) and Moses and Monotheism (1939 [1934-1938] / 1996). Thus, one of our main goals was to build a line of direction from the concept of psychic trauma, tacking the knowledge of all these texts, clarifying and agglutinating the main theoretical considerations of Freud on the subject, its dynamic and economy at different times of the work, thus forming a scene from the theory of trauma. The desire to recall the trauma and learn the concept in depth was the reason we decided to revisit Freud and his theories on psychic trauma in chronological order. Revisit texts on the subject since the early work in psychoanalysis, we are not only focused on articles dealing with, but extending ourselves to those little known that in many cases, already anticipated the major theoretical outcomes of the classic texts. Many questions arose during the work on what would have actually changed in the Freudian about it, so we follow Freud's work looking for these changes. At the end of this route, we concluded that even with many changes throughout the course of Freud's work in relation to psychic trauma, much of it devoted to statements by the author, were reconsidered and revalidated, especially in his article Moses and Monotheism. Possibly the wars and the living conditions of Freud at the end of his life, made him return to the psychic trauma and assign importance to him again, especially as a triggering factor of the neuroses and factually stating that every neurosis is a traumatic neurosis. Also worth noting that, as we assumed at first the quantitative character (excessive) is undoubtedly the defining characteristic of the psychic trauma and the only one that was never set aside, which makes Freud's theories on this subject timeless.